Salt Tolerance Mechanism of the Rhizosphere Bacterium JZ-GX1 and Its Effects on Tomato Seed Germination and Seedling Growth - Li, Pu-Sheng; Kong, Wei-Liang; Wu, Xiao-Qin (Frontiers in Microbiology, 2021)
Salinity is one of the strongest abiotic factors in nature and has harmful effects on plants and microorganisms. In recent years, the degree of soil salinization has become an increasingly serious problem, and the use of plant growth-promoting rhizobacteria has become an option to improve the stress resistance of plants. In the present study, the salt tolerance mechanism of the rhizosphere bacterium Rahnella aquatilis JZ-GX1 was investigated through scanning electron microscopy observations and analysis of growth characteristics, compatible solutes, ion distribution and gene expression. In addition, the effect of JZ-GX1 on plant germination and seedling growth was preliminarily assessed through germination experiments. R. aquatilis JZ-GX1 was tolerant to 0%–9% NaCl and grew well at 3%. Strain JZ-GX1 promotes salt tolerance by stimulating the production of exopolysaccharides, and can secrete 60.6983 mg/L of exopolysaccharides under the high salt concentration of 9%. Furthermore, the accumulation of the compatible solute trehalose in cells as the NaCl concentration increased was shown to be the primary mechanism of resistance to high salt concentrations in JZ-GX1. Strain JZ-GX1 could still produce indole-3-acetic acid (IAA) and siderophores and dissolve inorganic phosphorus under salt stress, characteristics that promote the ability of plants to resist salt stress. When the salt concentration was 100 mmol/L, strain JZ-GX1 significantly improved the germination rate, germination potential, fresh weight, primary root length and stem length of tomato seeds by 10.52, 125.56, 50.00, 218.18 and 144.64%, respectively. Therefore, R. aquatilis JZ-GX1 is a moderately halophilic bacterium with good growth-promoting function that has potential for future development as a microbial agent and use in saline-alkali land resources.